F KELAYAKAN FINANSIAL AGROFORESTRI DAN KEBUTUHAN HIDUP LAYAK PETANI DI DESA LAMBUSANGO KECAMATAN KAPONTORI KABUPATEN BUTON - agussalim Mando; Sitti Marwah; Rosmarlinasiah Rosmarlinasiah; Satya AgustinaLaksananny; Hafidah Nur; Lisnawati Hamdu (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2024)
The increase in population and basic needs has led to an increase in the need for larger agricultural areas and to be cultivated more intensively. Based on this, optimal land processing activities are needed for maximum results to address increasing needs, by implementing an agroforestry system. Agroforestry provides increased harvest intensity which in the end is able to provide additional output, even though the area of ​​cultivated land is very limited. The aim of this research is to determine the financial feasibility of agroforestry and the needs for a decent living in Lambusango Village, Kapontori District, Buton Regency. The population in this study were people who had an agroforestry planting pattern in Lambusango Village, consisting of 25 heads of families (HoF). Thus, the sample size in this study was determined using the census method. The data analysis used is analysis of financial feasibility and decent living needs (DLN). The results of this research indicate that agroforestry activities in Lambusango Village are financially feasible, with the agroforestry pattern that provides the greatest benefits, namely the Agrosilvopostura II pattern with an NPV value of Rp. 121,310,123,- BCR value of 2.74 and IRR value of 9%. Business of agroforestry systems in Lambusango Village with net income of IDR. 10,576,369/year has not been met based on Decent Living Needs (KHL) of IDR 24,000,000/year. Keywords: Agroforestry, Decent Living Feasibility, Financial Feasibility, Lambusango Village